Irony: The Gap Between Occupational Risks and Nurse Wages from a Legal Perspective - Legi, Arfi Nofri; Ismail; Iryani, Dewi (International Journal of Science and Society, 2025)
Nurses, as the backbone of healthcare services in Indonesia, face high multidimensional occupational risks, encompassing biological, physical, psychosocial, and legal hazards. Ironically, these high risks are not compensated with fair wages, as many nurses still receive remuneration below feasibility standards. This research aims to analyze the fundamental gap between occupational risks (Das Sein) and wage justice (Das Sollen) from a legal perspective. Using a normative-juridical method supported by the Theory of Distributive Justice and the Theory of Legal Protection, this study dissects the regulatory architecture of the healthcare sector’s wage system. The findings identify three primary juridical obstacles: First, the current wage system fails to apply a fair principle of proportionality between the level of risk and the amount of remuneration. Second, a crucial operational norm vacuum exists due to the absence of a Ministry of Health Regulation, which is mandated by Government Regulation (PP) No. 28 of 2024 to technically implement risk factor calculations. Third, wage justice is hampered by institutional weaknesses, including the limitations of PPNI as a professional organization lacking the formal bargaining power of a trade union, and insufficient state supervision.